Phonetic Transcription of Language ‘Baso Palembang Sari-Sari’ in Local Communication - Wahyuni, Sri; Mayrita, Hastari; Somad, Saifus (Faculty of Humanities, Universitas Jenderal Soedirman, 2024)
The problem raised in this study is how to explore the phenomenology of daily Palembang language. This study aims to analyze the phonetic transcription of Palembang language (Baso Palembang Sari-Sari) using the General Linguistic Theory proposed by Chaer. Through an analysis of various everyday expressions in Palembang, such as greetings, expressing gratitude, saying goodbye, apologizing, introducing oneself, and family terms, this research identifies phonetic and phonological differences between Palembang and Standard Indonesian. The Palembang Sari-Sari language was chosen due to its uniqueness as a regional language widely used in daily interactions in Palembang. The research method used is descriptive qualitative. The data sources were obtained from recordings of conversations between the author and native speakers of Palembang, based on foreign language learning syllabi and Palembang language dictionary documents. The data validity check technique used was peer debriefing. From the conversations, 29 Palembang Sari-Sari vocabulary items were obtained. Additionally, 60 Palembang Sari-Sari vocabulary items were found in the document analysis. Some distinctive features of the Palembang language identified include the use of diphthongs, voiced velar fricative [ɣ], open vowels [ɔ] and [ɛ], and the characteristic glottal stop [ʔ]. This phonetic analysis also reflects how these phonological variations relate to the Palembang language's more relaxed and informal structure. The findings of this study provide insights into the phonological practices of regional languages, which are essential to explore further in the context of applied linguistics. This research is expected to serve as a reference for learning regional languages, particularly for foreign speakers interested in exploring the diversity of the Indonesian language.